The prediction of estrus synchronization in Awassi ewes by vulvar bi-ometry and vaginal cytology - Al-Fatllawy, Hella J. (Journal of Kerbala for Agricultural Sciences, 2017)
The characteristics of exfoliated vaginal cells and vulvar biometry following estrus synchronization via insertion of vaginal sponges impregnated with 6-Methyl- 17- Acetoxyprogesterone (MAP) were investigated with the aim to predict estrus in ten adult Awassian ewes .The animals were maintained on green and concentrated ration with water ad libitium . All measurements in the ewes were taken before insertion of intravaginal sponges and at 0hrs , 24hrs , 72hrs after removed of intravaginal sponges. Nine out of ten ewes showed estrus behavior in synchronization rate 90%.The results of vaginal cytology showed dominancy of parabasal cells 49.9% before insertion of intravaginal sponges, and dominancy of intermediate cells 62.4% at 0 hour after removed of intravaginal sponges , while at 24hrs and 72 hrs. the dominant cells were nucleated superficial cells and intermediate cells in percentage rate of 44.3% and 41.8% respectively. The results showed that the measurements of vulvar biometry of synchronized ewes during the study period increase in the vertical dimension of vulva significantly (P≤0.05) only after 24hrs of removing of intravaginal sponges.